Intensive Glucose Control and Blood Pressure Reduction Additive in Type 2 Diabetes Mellitus - Jacobson, Anne (MD Conference Express, 2008)
Interventions that are designed to lower blood pressure or increase glucose control both improve outcomes in patients with type 2 diabetes mellitus. Together, these strategies provide even greater protection against diabetes-related complications, according to new findings from the Action in Diabetes and Vascular Disease [ADVANCE] trial.